2021
DOI: 10.3390/genes12070994
|View full text |Cite
|
Sign up to set email alerts
|

Store-Independent Calcium Entry and Related Signaling Pathways in Breast Cancer

Abstract: Known as a key effector in breast cancer (BC) progression, calcium (Ca2+) is tightly regulated to maintain the desired concentration to fine-tune cell functions. Ca2+ channels are the main actors among Ca2+ transporters that control the intracellular Ca2+ concentration in cells. It is well known that the basal Ca2+ concentration is regulated by both store-dependent and independent Ca2+ channels in BC development and progression. However, most of the literature has reported the role of store-dependent Ca2+ entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…However, the biological functions of ZNF791 and MED18 in BRCA are largely unknown, making it impossible to infer the plausibility of associations between the two sites and BRCA survival. Moreover, the cellular pathway clearly demonstrated that AIRS was associated with several signaling pathways, such as oxidative phosphorylation ( 33 ), proteasome ( 34 ), and calcium signaling pathway ( 35 ). These pathways are all promising targets for the treatment of BRCA, which suggests the AIRS as new targets for BRCA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the biological functions of ZNF791 and MED18 in BRCA are largely unknown, making it impossible to infer the plausibility of associations between the two sites and BRCA survival. Moreover, the cellular pathway clearly demonstrated that AIRS was associated with several signaling pathways, such as oxidative phosphorylation ( 33 ), proteasome ( 34 ), and calcium signaling pathway ( 35 ). These pathways are all promising targets for the treatment of BRCA, which suggests the AIRS as new targets for BRCA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To what extent Orai1 proteins have the potential to cause cancerous remodelling is dependent on the cancer type and the particular context [ 31 ]. Furthermore, Ca 2+ is essential for human brain tumour glioblastoma invasion [ 65 ] and for invasive stimuli in breast cancer [ 66 , 67 , 68 ]. Melanoma cells are dependent on Orai1 which plays a central role in cell migration and proliferation [ 69 , 70 ].…”
Section: Calcium and Its Role In Human Diseasesmentioning
confidence: 99%
“…ORAI1 can also be activated distinctly from the canonical Ca 2+ store depletion-mediated STIM1-dependent pathway, referred to as store-independent Ca 2+ entry (SICE) [ 10 ]. SICE includes the activation of ORAI1 by the secretory pathway Ca 2+ -ATPase 2 pump (SPCA2), which is implicated in the promotion of tumorigenesis in breast cancer [ 11 ].…”
Section: Introductionmentioning
confidence: 99%